AN ANALYSIS OF LEARNING ACTIVITIES FOR PROBLEM-BASED LEARNING IN THE PROCEDURE TEXT LESSON PLAN - Hasanah, Anggi Ulul; Ambarini, Ririn; Shiang, Grace Yeh (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
It has been a big issue that the quality of teacher candidates or teachers in Indonesia in conducting learning activities in lesson plans. This research aims to analyse the appropriateness between main learning activities with the syntax of problem-based learning and student worksheet. There are five syntaxes which analysed in this research including student orientation to the problem, organizing students, individual and group research guide, development and presenting the work, and analyse and evaluate the problem-solving process. This study employed descriptive qualitative method. The data was the procedure text lesson plan designed by English teacher from senior high school. The data were collected using observation sheet. Data reduction, data display, and conclusion drawing were used to analyse this research data. The findings of this research reveal that teacher creates systematically main learning activities which is required the core of each syntax of problem-based learning. In addition, the main learning activities had implemented student-centered learning through interactive questions and answers, individual assignments, pair assignments and group discussion. It also finds that teacher conducted student’s worksheet which is in accordance with the learning activities and served actual or daily context of situations being discussed as the point of Problem-based Learning model.